Synthesis and Antibacterial Activity of 6-bromo-2-(o-aminophenyl)-3-amino-Quinazolin-4(3H)-one from 6-bromo,2-(o-aminophenyl)-3,1-benzoxazin-4(3H)-one. - Osarodion, Osarumwense Peter (European Journal of Applied Sciences, 2023)
Introduction: Quinazolinone derivatives reveal various medicinal properties such as analgesic, anti-inflammatory and anticancer activities, as well as antimicrobial activity. These heterocycles are valuable intermediates in organic synthesis. Methods/Experimental: The compound, 6-bromo,2-(o-aminophenyl)-3,1-benzoxazin-4(3H)-one (1) was synthesized by dissolving 5-bromo anthranillic acid in 100 ml of pyridine. To this reaction mixture o-amino benzoyl chloride stirring at room temperature for 30 minutes this was refluxed with 75 mL of hydrazine hydrate for 3 hrs. at 120-1300C. the reaction mixture was allowed to cool to room temperature to give 6-bromo-2-(o-aminophenyl)-3-amino-Quinazolin-4(3H)-one (2). These Compounds were evaluated for their bacterialrial activity (against some gram positive and gram-negative microorganism) and antifungal activity (against Candida albicans). Study Design: This study was experimentally design and the antibacterial activity was evaluated against some microorganism, Staphylococcus aureus, Bacillus species, Aspergillus Species, Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumonia, and candida albicans. Result: The compounds exhibited significant antibacterial activity with a zone of inhibition in the range of 10 – 16mm in comparison to control. Conclusions: From our findings, the compounds synthesized have higher antibacterial activities as compared to Ciprofloxicin (CPX) and Ketonaxol (PEF) standard antibacterial drugs.